Optical nanoscopy and novel microscopy techniques - Xi, Peng
"Many new methods in light and super-resolution microscopy have been developed over the last few years. This edited volume overviews the latest advances in microscopy, complete with experimental methods and data analysis of the results. Each chapter begins with a brief description of the principles of the technique for clarity and concludes with a set of problems. Cutting-edge microscopy techniques presented include STED, PALM/STORM, and light sheet microscopy"--Provided by publisher.